HYPERVASCULARISATION OF REGENERATIVE NEUROMA - Chaikovsky, Yu.В. (World of Medicine and Biology, 2019)
Although the post-traumatic morphological changes as well as those taking place in the course of nerve trunks regeneration have been extensively studied, there are few quantitative data on nerve fibers and microvessels of the regenerative neuroma. This study is aimed at obtaining the morphometric data on nerve fibers and capillaries of the regenerative neuroma of the rats’ sciatic nerve 3, 6, 12 and 24 weeks after neurotomy. The study has revealed a significant increase in the density of capillaries and nerve fibers in regenerative neuroma at the initial stages of the experiment. By 24 weeks after surgery, these indicators were normalized. It may be concluded that hypervascularisation of the regenerative neuroma of the peripheral nerve after its injury provides for the metabolic and plastic needs of regenerating axons and connective tissue cells.
Keywords: regenerative neuroma; sciatic nerve; hypervascular; rats